TERAPI AL-QUR’AN: STUDI LIVING AL-QUR’AN TENTANG METODE RUQYAH SYAR’IYYAH (At-Tibyan, 2023)
This article discusses the reality of Muslims in how they perceive the Koran by using certain verses in the practice of ruqyah (Qura’nic healing). It is the Ruqyah Quaranic Healing International (QHI) in Lampung Region which in practice uses verses from the Koran as a means of curing client’s illnesses. This research uses a qualitative approach using primary and secondary data sources explored using snowball sampling. Based on the results of interviews and observations, data was found that: First, QHI's Quar'anic Healing reception practice of the Koran is classified as ruqyah syar'iyyah. Second, ruqyah syari’yyah and clients understand ruqyah as a form of receiving the Koran which is believed to have supernatural powers that can cure both psychological and physical illnesses. From a da'wah perspective, in the mass ruqyah process a social network is built between the raqi and the client. Third, the practice of receiving the Koran in the ruqyah process is able to form individuals who are obedient to Allah SWT.